Interactive learning: The use of virtual reality in UiTM education system / Anis Hasliza Abu Hashim …[et al.] - Abu Hashim, Anis Hasliza; Ibrahim, Norfiza; Hasnan, Mazliana; Jamaludin, Roslan (2006)
Current rapid development in Virtual Reality (VR) technology has led to many successful applications that are very useful in many fields such as in learning and training in many disciplines. VR technologies have been evolving during the past few years, leaving research laboratories and finding application in a number of areas. Virtual reality promises the creation of environments that are vivid, lifelike. and highly interactive, and where the user will be able to emerge in a synthetic world that may not exist or may be too difficult or too dangerous to visit in a real-world situation. Many examples of where VR has been used for educational purposes around the world. Each has shown a level of success even though the technology was extremely limited. It seems that the successful of the area was attributed to the flexibility offered by the virtual environment. There is no doubt that the students who used a VR based system enjoyed themselves. It is highly likely that this factor contributed to the sense of fulfillment that the students reported. The main objective of this paper is to introduce the use of virtual reality in educational field and convey the knowledge and the applications that have been done and currently being done in the virtual reality area. UiTM could benefit the technology of VR in many ways as this technology is becoming very well-known and easy to access.